1H NMR characterisation of the lipid fraction and the metabolite profiles of Fossa (pit) cheese. (March 2019) - Scano, Paola; Cagliani, Laura R.; Consonni, Roberto
Abstract: Fossa cheese is a typical Italian cheese characterised by ripening in pits dug in tuffaceous rock. In this work, 1 H NMR spectroscopy was applied to characterise the lipid fraction and the metabolite profile of Fossa cheese produced with sheep's milk. Samples were collected before and after ripening in different pit environments. The higher levels of free amino acids (FAAs) found in samples suggest that cheeses underwent a strong proteolytic process. Differences in quantity and variety of FAAs were influenced by the two ripening environments. Diacylglycerols and butyric acid, which can be linked to lipolysis, were detected in all the samples. Longer ripened samples had higher contents of rumenic acid (18:2 cis -9, trans -11) and glycerol, and lower contents of lactate and citrate. The presence of tyramine was observed by two-dimensional NMR, while cadaverine was not detected in the samples.